The Impact of Incorporating Socio-Cultural Elements into English Language Teaching at Algerian Universities. The Case of First-Year LMD Students of English at the University of Souk-Ahras - Mounira MERADJI (My University, 2025)
Abstract This dissertation investigates the impact of incorporating socio-cultural elements into English language teaching (ELT) at Algerian universities, focusing on first-year LMD students at Mohammed Cherif Messaadia University, Souk Ahras. The study explores how the inclusion of socio-cultural content influences students' language learning, motivation, cultural awareness, and communicative competence. It also examines the extent to which these elements are currently integrated into university-level English teaching. A mixed-methods approach was employed using questionnaires as the sole data collection tool. Both quantitative data (from closed-ended questions) and qualitative insights (from open-ended questions) were collected from 30 students and 10 English teachers. The findings indicate that the integration of socio-cultural elements enhances student motivation, strengthens cultural awareness, and improves contextual language use. However, the results also reveal inconsistencies in how these elements are implemented, often relying on individual teacher initiative rather than structured curriculum guidance. --------------- Résumé Ce mémoire étudie l’impact de l’intégration des éléments socio-culturels dans l’enseignement de la langue anglaise au sein des universités algériennes, en se concentrant sur les étudiants de première année LMD à l’université Mohammed-Chérif Messaadia de Souk Ahras. L’objectif est d’analyser comment ces éléments influencent l’apprentissage de la langue, la motivation, la conscience culturelle et la compétence communicative des étudiants, ainsi que de déterminer dans quelle mesure ils sont effectivement intégrés dans l’enseignement de l’anglais au niveau universitaire. Une approche méthodologique mixte a été adoptée, basée exclusivement sur des questionnaires. Les données quantitatives (questions fermées) et qualitatives (questions ouvertes) ont été recueillies auprès de 30 étudiants et 10 enseignants d’anglais. Les résultats montrent que l’intégration d’éléments socio-culturels favorise la motivation des apprenants, renforce leur conscience interculturelle et améliore leur capacité à communiquer dans des contextes réels. Toutefois, l’étude met en lumière une application irrégulière de ces éléments, souvent tributaire de l’initiative individuelle des enseignants, faute de directives pédagogiques claires. --------------- الملخص تتناول هذه الدراسة أثر إدماج العناصر السوسيو-ثقافية في تعليم اللغة الإنجليزية في الجامعات الجزائرية، مع التركيز على طلبة السنة الأولى من نظام "أل.أم.دي" بجامعة محمد الشريف مساعدية – سوق أهراس. تهدف الدراسة إلى معرفة مدى تأثير دمج هذه العناصر في تحسين تعلم اللغة، رفع الدافعية، تنمية الوعي الثقافي، وتعزيز الكفاءة التواصلية لدى الطلبة. كما تسعى إلى تقييم مدى إدماج هذه العناصر في برامج تعليم اللغة الإنجليزية على مستوى التعليم العالي. تم اعتماد منهجية مختلطة باستخدام الاستبيانات فقط كأداة لجمع البيانات. وقد تم جمع بيانات كمية (من الأسئلة المغلقة) وبيانات نوعية (من الأسئلة المفتوحة) من 30 طالبًا و10 أساتذة للغة الإنجليزية. أظهرت النتائج أن إدماج العناصر السوسيو-ثقافية يساهم بشكل واضح في تحفيز الطلبة، وزيادة وعيهم بالاختلافات الثقافية، وتحسين قدرتهم على استخدام اللغة في السياقات المناسبة. ومع ذلك، أبانت الدراسة عن وجود تباين في تطبيق هذه العناصر، حيث يتم الاعتماد غالبًا على المبادرات الفردية للأساتذة في ظل غياب توجيهات منهجية واضحة
Keywords: English language teaching; socio-cultural elements; intercultural competence; cultural awareness; motivation; Algerian university; تدريس اللغة الإنجليزية، العناصر السوسيو-ثقافية، الكفاءة التواصلية، الوعي الثقافي، الدافعية، الجامعة الجزائرية: enseignement de l’anglais; éléments socio-culturels; compétence interculturelle; conscience culturelle; université algérienne